PENGARUH PENERAPAN METODE DISKUSI TERHADAP KREATIVITAS BELAJAR PAK SISWA KELAS VIII SMP NEGERI 1 PAGARAN TAHUN PEMBELAJARAN 2019/2020 - Sianipar, Evi Vitriani (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
This research aims to find out the influence of positive and significant influence Between Application of Discussion Methods on Learning Creativity Student of Christian Religious Education Classroom VIII Public Middle School 1 Pagaran 2019/2020 Academic Year, with the hypothesis there are positive and significant influence between the Implementation of the Discussion Methods of Creativity learn Christian Religious Education of student Class VIII Students of Public Middle School 1 Pagaran Learning Year 2019/2020.This research uses a quantitative inferential approach, with the population all of Grade VII stude nts of Public Middle School 1 Pagaran Learning Year 2019/2020 that amounts to 125 people with a sample of 39 people. The data collected with inquiries closed as much as 42 items composed by the authors based on the indicator variable according to the theory. Questionnaire trials was done to 30 students who is not research respondents, and has been in the test validity and reliability. The results of data analysis suggests that there is the influence of a positive and significant between the implementation of the Discussion of Creativity Learn Christian Religious Education in Class VIII of Public Middle School 1 Pagaran Learning Year 2019/2020 with the coefficient of determination (r^2) = 47.33% and a significant test Influence obtained by Fcount of 32.36 4.11, means that H0 is rejected and Ha received.Keywords: Discussion Method, Student Learning Creativity.